World military history bibliography : premodern and nonwestern military institutions and warfare - Hacker, Barton C., 1935- (History of warfare, 2003)
Preclassical and indigenous nonwestern military institutions and methods of warfare are the chief subjects of this annotated bibliography of work published from 1967 to 1997. It emphasizes historical studies of military organization and relations between military and other social institutions.